Response of Some Anatomical Properties and Growth of Calotropis Procera (AIT) R.Br to Method Adition of Nano-iron, Zinc and Organic Fertilizer Growth - Abdulameer Ali Yaseen (Journal of Global Pharma Technology, 2018)
Pots experiment was conducted in a nursery affiliated to the Al-Qasim town during the spring season of (2016 - 17). The aim of the experiment was to find the effect chelated nano iron and zinc fertilizer(seven concentration) in two application methods: foliar applied (0 ,1Fe, 2Fe,1Zn, 2Zn, 1Fe +1Zn, 2Fe+2Zn) g.L-1 and fertigation was included (0 ,80Fe, 160Fe,80Zn, 160Zn, 80Fe +80Zn, 160Fe +160Zn) mg.L-1 and organic fertilizer Drin (0.0 , 5) ml.L-1 and their interactions on growth parameter, and the production of active substances as well as mineral and organic content of the leaves and some anatomical features of Calotropis procera (Ait.) R.BR. The experiment was designed in a randomized complete blocks (RCBD), in a Factorial arrangement (7*2*2) with three replications. The Least Significant Difference (LSD) at 0.05 probability level was used to compare treatments means, whenever treatment effects were evident. The nano iron and zinc fertilizer and the methods application (first treatment), as well as organic fertilizer Drin, were applied at (6- 8 fully expanded leaves) stage. While the second application of nano fertilizer and organic fertilizer was after three month from the first treatment. The results showed that the use of doubled recommended of nano-iron was recorded the highest leaf area. Doubled concentrations for nano zinc was recorded the highest stem diameter and cortex thickness.Foliar application of nano fertilizer had given highest stem diameter, leaf area, the vessel diameter in the vascular bundles of stem. Foliar application of organic fertilizer (5ml. L-1) increased all parameters studied except leaf area and cortex thickness, while the negative impaction on the vessel diameter in the vascular bundles of the stem. The interaction between nano fertilizer and application method by combinations significant increased all parameters studied. The interaction between nano fertilizers and organic fertilizer increased all parameters studied. The Interaction between application method and organic fertilizer showed did not reveal a significant difference in all parameters studied except leaf area. And interaction between study factors revealed a significant improvement of the C. procera plant in all parameter studied.Keywords: Nano iron and Zinc, Application method, Calotropis procera.